(untitled) (International Journal of Medicine and Medical Sciences, 2019)
A prospective study was carried out on 1125 surgeries for the incidence of surgical site infections (SSIs). The etiologic agent was isolated, identified and the antibiotic susceptibility pattern was determined using standard methods. The risk associated with SSIs was assessed by multivariate regression logistic analysis. A case control study was carried out for the outcome of SSIs. The outcomes measured were: length of intensive care unit (ICU) stay (in days), length of ward stay (in days), costs incurred (in rupees) by the patient, and mortality rate. The results indicated that 12% of patients undergoing surgery developed SSI. Staphylococcus aureus (33%) and Enterococcus spp. (33%) were the commonest etiologic agents. Patients with SSIs had a significantly extended ICU and ward stay (p<0.001), and incurred higher hospital costs (p<0.001) when compared to those who did not develop SSIs. The mortality rate was high in patients who developed SSIs. The risk factors associated with SSIs were age above 45 years (p=0.012), female (p=0.070), diabetic status (p<0.001) and surgeries such as gastrectomy, prostatectomy, hysterectomy, cholecystectomy and appendectomy. Surgical site wound infection, though preventable, still remains as high as 12%. Determining the antimicrobial patterns of the organisms causing SSIs will enable institutions to restrict the use of antimicrobials and take active measures in preventing the spread of drug resistance in a hospital.